Consumer protection against unfair market practices on the financial market - Horosz, Piotr (The Opole Studies in Administration and Law, 2022)
The article focuses on the issues of consumer protection against unfair market practices in the financial sector, discussing in this respect the legal regulations contained in the provisions of the Act on Counteracting Unfair Market Practices. When discussing market practices detrimental to the interests of consumers, especially misleading practices and aggressive market practices, the author points to a general prohibition of such practices, also applicable to consumers using financial services. At the same time, the author emphasizes that the protection of consumers against unfair market practices in the financial market is strengthened in comparison with the protection of consumers in other markets. This is due in particular to the functioning of specific bodies on the financial market, in particular the Polish Financial Supervision Authority and the Financial Ombudsman, which, within their general powers, may also take measures to protect consumers of financial services against unfair market practices.